If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18y = 9y + 18 Reorder the terms: 18y = 18 + 9y Solving 18y = 18 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 18y + -9y = 18 + 9y + -9y Combine like terms: 18y + -9y = 9y 9y = 18 + 9y + -9y Combine like terms: 9y + -9y = 0 9y = 18 + 0 9y = 18 Divide each side by '9'. y = 2 Simplifying y = 2
| 5(x-4)+4(x-6)=7 | | 2-x+5=7-3 | | 5x+4+26=90 | | -x+2+7x=-2+2x+16 | | N^2+6n-21=0 | | 5m-4=2m-22 | | 22x+22(x-9)=45 | | 6v+2v+3= | | x^4+72x^2+94400=0 | | 2(4)+p=35 | | -16t(t+1)(t-5)=0 | | 2x+4(x-5)=2(x-4) | | 8m-11+2m-4=180 | | -x+3+14x=-6+4x+36 | | 2x+6-x-3=40 | | 0.09x+0.19(x+7000)=3570 | | (3x-3)=48 | | 3x^2-2y=48 | | (3x-3)=58 | | 2x^2+3x-23=3 | | 5b-22=7b+12 | | 4x-5(2x+1)=6x+1 | | 4x-5(2x+1)=-6x+5 | | 0.3(x+-100000)=1000000 | | 4x-5(2x+1)=1x+-5 | | 38ln(x)=79 | | 38lnx=79 | | 4x-5(2x+1)=0x+-5 | | -(3x-5)-(5x-2)+4=-8(x-4)-(3x+4)+4 | | 4x-5(2x+1)=-0x+-5 | | x^2y+4y+5x^2+20= | | -12=-7u |